DIFFERENTIATED E-MODULES BASED ON CASE METHOD THROUGH WEB GOOGLE SITES ON STUDENT LEARNING OUTCOMES ON VIBRATION AND WAVE CONCEPTS IN NAVIGATION SYSTEMS - Yuna Sutria; Rajo Hasim Lubis (Universitas Labuhanbatu, 2026)
Purpose – This study aims to develop and test the feasibility, practicality, and effectiveness of a Case Method-Based Differentiated E-Module through the Google Sites platform.Methodology – This research is a research and development (R&D) using the 4D model (Define, Design, Develop, Disseminate). The research instruments included validation sheets from material and media experts, lecturer and student response questionnaires for practicality testing, and learning outcome tests (pretest-posttest) for effectiveness testing. The research subjects consisted of 32 students with various learning styles (visual, auditory, reading, and kinesthetic).Findings – The results of the study indicate that the developed E-Module is highly feasible to use, with V-Aiken indices of 0.81 (Very Valid) from material experts and 0.78 (Quite Valid) from media experts. In terms of practicality, this product received a score of 86.99% from the lecturer and 83.6% from students, placing it in the very practical category. The effectiveness test showed that 69% of students met the high effectiveness criteria for improving cognitive learning outcomes after using the module.Contribution – This product serves as a reference model for educators in implementing the Independent Curriculum, which is inclusive, adaptive, and able to facilitate the personal needs of each student in understanding abstract physics concepts